2021
DOI: 10.5812/ijcm.111509
|View full text |Cite
|
Sign up to set email alerts
|

Health Belief Model and Determinants of Breast Self-examination Performance

Abstract: Objectives: This study aimed at performing a path analysis to assess the parameters of the health belief model concerning BSE. Methods: The present descriptive cross-sectional study at a health care center, affiliated with Islamic Azad University Tehran, Faculty of Medicine in the northwest of Tehran, Iran was conducted from May to June 2018. The champion’s HBM scale, breast cancer knowledge test was assessed in all participants. The SPSS-22 and Lisrel-8.8 software, using statistical path analysis, were used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In this study women with education level ranging from primary to tertiary had increased odds of BC screening compared to women with informal education. This was also observed in the studies of Ayanore et al, 29 , Opoke et al 31 , Mousavi et al 32 , and Islam et al 33 . High level of formal education which is one of the indicators of high socioeconomic status has a positive influence on health-seeking behaviour.…”
Section: Discussionsupporting
confidence: 73%
“…In this study women with education level ranging from primary to tertiary had increased odds of BC screening compared to women with informal education. This was also observed in the studies of Ayanore et al, 29 , Opoke et al 31 , Mousavi et al 32 , and Islam et al 33 . High level of formal education which is one of the indicators of high socioeconomic status has a positive influence on health-seeking behaviour.…”
Section: Discussionsupporting
confidence: 73%
“…In our study, less than half of the students confirmed that they had performed BSE and that some of them performed BSE 1 month prior to the study. Similarly, in few other studies, one third of female students and women performed BSE; however, all participants did not practice BSE regularly ( Alam, 2006 ; Aghamolaei et al, 2011 ; Kim et al, 2019 ; Lechner et al, 2004 ; Mousavi et al, 2018 ; Tavafian et al, 2009 ). Therefore, our study calls for advocacy and nurse-led educational interventions to improve the knowledge of adolescent girls and women on the importance of performing BSE.…”
Section: Discussionmentioning
confidence: 74%
“…The highest mean and SD were noted in the item “Doing BSE will take too much time” and the lowest mean and SD in the item “Doing BSE during the next year will make me worry about BC.” Our participants disagreed to most statements regarding the barriers in performing BSE. In contrast, previous studies have reported various other factors as barriers to BSE, including lack of knowledge, absence of any symptoms ( Al-Naggar et al, 2011 ; Hanson et al, 2019 ; Ng’ida et al, 2019 ; Tabari et al, 2017 ), low knowledge level of how to do BSE, busyness ( Abo Al-Shiekh et al, 2021 ), leaving the condition to God ( Mousavi et al, 2018 ), fear of being diagnosed with BC ( Al-Naggar et al, 2011 ; Hanson et al, 2019 ), and socio-cultural and environmental factors ( Akhtari-Zavare et al, 2015 ). BSE training programs are strongly recommended to reduce these barriers.…”
Section: Discussionmentioning
confidence: 90%
“…Since healthcare professionals play significant roles in the lives of women with breast cancer, it is not surprising that they were the primary source of information. However, some studies revealed that personal communication with some healthcare professionals revealed that breast cancer patients are primarily given verbal information because most have low literacy levels [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%